2009
DOI: 10.1128/aac.00548-09
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of Leishmania donovani Promastigote and Amastigote Stages to Antileishmanial Reference Drugs: Practical Relevance of Stage-Specific Differences

Abstract: The in vitro susceptibilities of the reference strain Leishmania donovani MHOM/ET/67/L82 to sodium stibogluconate, amphotericin B, miltefosine, and the experimental compound PX-6518 were determined for extracellular log-phase promastigotes, established axenic amastigotes, fresh spleen-derived amastigotes, and intracellular amastigotes in primary mouse peritoneal macrophages. Susceptibility to amphotericin B did not differ across the various axenic models (50% inhibitory concentrations [IC 50 ], 0.6 to 0.7 M),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
166
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(188 citation statements)
references
References 37 publications
13
166
1
1
Order By: Relevance
“…(De Muylder et al, 2011). Compounds active against axenic parasites might be unable to reach the intracellular amastigotes, because of their inability to cross the host cell membranes, or maintain stability under low pH, whereas other compounds may need to be metabolized by macrophages to gain activity (Vermeersch et al, 2009). This is in accordance with previous studies, which found that only 4% of their hits identified in a promastigote primary screening were actually active in an intracellular context (Siqueira-Neto et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…(De Muylder et al, 2011). Compounds active against axenic parasites might be unable to reach the intracellular amastigotes, because of their inability to cross the host cell membranes, or maintain stability under low pH, whereas other compounds may need to be metabolized by macrophages to gain activity (Vermeersch et al, 2009). This is in accordance with previous studies, which found that only 4% of their hits identified in a promastigote primary screening were actually active in an intracellular context (Siqueira-Neto et al, 2010).…”
Section: Discussionsupporting
confidence: 80%
“…Despite the more complex and labor-intensive protocol, the intracellular amastigote model has been cited as the golden standard for in vitro Leishmania drug discovery research (9,28). The results showed in this work reinforce the potential leishmanicidal activity of the oxygenated analogues of marine 3-alkylpyridine alkaloids.…”
Section: Pharmacologysupporting
confidence: 70%
“…Vermeersch et al (28) recently recommended that the intracellular amastigote model could be employed as the 'gold standard' for antileishmanial in vitro evaluation. Amastigote forms are the stage of parasite found in the mammalian host and responsible for the human disease.…”
Section: Pharmacologymentioning
confidence: 99%
“…On the other hand, the lack of correlation between the results against promastigotes and amastigotes points to the need for using at least the intracellular stage in macrophages as the screening method to identify lead compounds against Leishmania. This need has been recognized, 25,31,32 and is possibly critical for reducing the attrition rates of drug discovery.…”
Section: Discussionmentioning
confidence: 99%